O grande deslocamento da violência - Confins (Confins)
The article is based on original maps produced using data from the Atlas of Violence published by the Institute for Applied Economic Research (Ipea) and the Brazilian Public Security Forum, showing huge spatial differences in the distribution of homicides. They associate the number of homicides recorded in each of the country's municipalities (represented by the size of the proportional circles) and the proportion of these homicides in relation to the municipal population (represented by a color gradation), while the background map is colored according to the municipal development index calculated by Firjan. The map drawn for the year 2021 confirms a clear evolution in relation to previous situations (1989, 1999, 2009 and 2019), a shift in crime towards the Northeast and North regions, while the number and proportion of homicides in the population fell rapidly in the main capitals of the Southeast.